Composites of poly(L‐lactide‐trimethylene carbonate‐glycolide) and surface modified SBA‐15 as bone repair material. (12th January 2018) - Wang, Jielin; Du, Beibei; Fan, Zhongyong; Li, Suming; Yun, Peng; Su, Feng
Abstract : This work aims to develop novel composites from a poly(L ‐lactide‐ co ‐trimethylene carbonate‐ co ‐glycolide) (PLTG) terpolymer and mesoporous silica (SBA‐15) nanofillers surface modified by post‐synthetic functionalization. SBA‐15 first reacts with a silane coupling agent, γ‐aminopropyl‐trimethoxysilane to introduce ammonium group. PLLA chains were then grafted on the surface of SBA‐15 through ammonium initiated ring‐opening polymerization ofL ‐lactide. Composites were prepared via solution mixing of PLTG terpolymer and surface modified SBA‐15. The structures and properties of pure SBA‐15, γ‐aminopropyl‐trimethoxysilane modified SBA‐15 (H2 N‐SBA‐15), PLLA modified SBA‐15 (PLLA‐NH‐SBA‐15), and PLTG/PLLA‐NH‐SBA‐15 composites were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, X‐ray diffraction, scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, transmission electron microscopy, N2 adsorption‐desorption, differential scanning calorimetry, contact angle measurement, and mechanical testing. The results demonstrated that PLLA chains were successfully grafted onto the surface of SBA‐15 with grafting amounts up to 16 wt.%. The PLTG/PLLA‐NH‐SBA‐15 composites exhibit good mechanical properties. The tensile strength, Young's modulus, and elongation at break of the composite containing 5 wt.% of PLLA‐NH‐SBA‐15 were 39.9 MPa, 1.3 GPa, and 273.6%, respectively, which were all higher than those of neat PLTG or of the composite containing 5 wt.% of pure SBA‐15. Cytocompatibility tests showed that the composites present very low cytotoxicity.